Penggunaan Media Tata Surya Untuk Meningkatkan Hasil Belajar IPA - Anisa Sinnatul Ula; Agung Setyawan (Smart Education, 2022)
Abstract: This study aims to improve student learning outcomes using Solar System media on Solar System material grade VI SDN Larangan Badung 2. The subjects of this study were grade VI students of SDN Larangan Badung 2, as many as ten people. This research is a Classroom Action Research (PTK) with the object of research in the form of cognitive abilities in Solar System material. The research was conducted as a cycle and divided into two cycles. Each cycle consists of two meetings. Solar System material is one of the materials that is quite difficult for students to understand. This material is complex and challenging to understand because the science is abstract. Learning activities in the classroom also tend to be monotonous and passive. Passive students usually indicate that these students lack understanding of the material provided. This is what causes the number of student learning outcomes to be low or can be said to be incomplete. Based on the study results, using Solar System media on Solar System material can improve student learning outcomes, and students become interested in participating in learning.Keywords: learning media; multimedia; Solar System Abstrak: Penelitian ini bertujuan untuk meningkatkan hasil belajar siswa menggunakan media Tata Surya pada materi Tata Surya kelas VI SDN Larangan Badung 2. Subjek penelitian ini adalah peserta didik kelas VI SDN Larangan Badung 2 sebanyak 10 orang. Penelitian ini merupakan Penelitian Tindakan Kelas (PTK) dengan objek penelitian berupa kemampuan kognitif dalam materi Tata Surya. Penelitian dilakukan dalam bentuk siklus dan dibagi menjadi dua siklus. Dalam tiap siklusnya terdiri atas dua kali pertemuan. Materi Tata Surya merupakan salah satu materi yang cukup sulit dipahami oleh siswa. Materi ini dianggap susah dan sulit untuk dipahami, dikarenakan ilmunya yang bersifat abstrak. Kegiatan pembelajaran di dalam kelas juga cenderung monoton dan menjadi pasif. Siswa yang pasif biasanya menandakan bahwa siswa tersebut kurang memahami terhadap materi yang diberikan. Hal ini yang menyebabkan banyaknya hasil belajar siswa cenderung rendah atau dapat dikatakan tidak tuntas. Berdasarkan hasil penelitian dapat disimpulkan bahwa penerapan media media Tata Surya pada materi Tata Surya dapat meningkatkan hasil belajar siswa dengan baik, siswa menjadi tertarik dalam mengikuti pembelajaran.Kata kunci: media pembelajaran; multimedia; Tata Surya